An approach to revolutionize cataract treatment by enhancing drug probing through intraocular cell line. Issue 1 (1st January 2018) - Wang, Ling; Liu, Weixian; Huang, Xionggao
ABSTRACT: The purpose of this study is to prepare and characterize solid lipid nanoparticles (SLN) of N-Acetyl Carnosine (NAC) to treat cataract since surgery necessitates equipments and professional help. Cataract is believed to be formed by the biochemical approach where the crystalline eye proteins lose solubility and forms high molecular weight masses. Added advantages of SLN of NAC (henceforth referred as SLN-NAC) in the study are reduced size, sustained release and better corneal penetration of drug. The method of preparation of SLN-NAC by Mill's method is unique in itself. The size of the SLN-NAC was 75 ± 10 nm in the range of ideal for penetration. The in-vitro release study and the SLN-NAC formulations prepared with Mill's method demonstrated sustained release up to 24 h following an initial burst after 1 h. The zeta potential of the prepared formulation was −22.1 ± 1 mV. Corneal permeation studies using goat corneas indicate that SLN-NAC penetration rate was higher than those from NAC eye drops. Corneal hydration studies indicated that the formulation caused no harm to the corneal cells. Therefore it may be concluded that SLN-NAC may revolutionize cataract treatment and reversal by improving drug permeation, reducing toxicity and no damage to corneal tissue.